Clinical spectrum and long-term outcomes of antibody-negative severe autoimmune encephalitis: a retrospective study - Li, Fangfang; He, Yu; Chen, Xiaoqian; Yang, Ali; Zhang, Jiewen; Zang, Weizhou (Frontiers in Immunology, 2025)
ObjectiveThe aims of the study were to characterize the clinical manifestations and outcomes of patients with antibody-negative severe autoimmune encephalitis (AE).MethodsThis retrospective, monocentric study recruited patients from the Neurology Department of Henan Provincial People’s Hospital between April 2017 and December 2023. All patients underwent neural antibody testing in both blood and cerebrospinal fluid (CSF) and met the diagnostic criteria for autoantibody-negative but probable severe AE, with available 1-year follow-up data.ResultsIn total, 124 patients with autoantibody-negative severe AE were analyzed. Among them, 27.4% achieved good functional outcomes at discharge. Older age (OR 1.034, 95% confidence interval [CI] 1.010-1.058, p = 0.004) and the presence of dyskinesia/dystonia (OR 8.463, 95% CI 3.282-21.820, p < 0.001) were predictive of poor short-term outcomes. At the 1-year follow-up, 54.8% experienced favorable long-term outcomes. Independent predictors of unfavorable long-term outcomes included older age (OR 1.076, 95% CI 1.018-1.136, p = 0.009), longer hospital stays (OR 1.264, 95% CI 1.105-1.446, p = 0.001), the presence of refractory status epilepticus (OR 14.765, 95% CI 1.759-123.935, p = 0.013) and higher CASE scores at discharge (OR 2.079, 95% CI 1.450-2.980, p < 0.001). Additionally, 30.6% of patients had relapsed, with refractory status epilepticus being an independent risk factor for relapse.ConclusionAlthough patients with antibody-negative severe AE experience significant disability in the early stages of their disease, the majority eventually regain independent functioning. Older age at disease onset, longer hospital stays, the presence of refractory status epilepticus and higher CASE scores at discharge may predict a poor long-term prognosis.